Kondisi Lalu Lintas, Jarak Tempuh, Kelelahan Berkendara, dan Motivasi Akademik Mahasiswa - Tristan Abdurrahman Qolbu Nafy; Ilham Nadhifa Luthfiansyah; Wahid Munawar (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Traffic congestion and long commuting distances have become common challenges for university students who travel daily to campus. These transportation-related conditions may increase driving fatigue and reduce students' psychological readiness to engage in academic activities. However, empirical evidence explaining the mechanism through which commuting conditions influence academic motivation remains limited. This study aimed to examine the effects of traffic conditions and commuting distance on driving fatigue and to investigate its implications for students' academic motivation. A quantitative correlational design was employed involving 150 university students in the Bandung metropolitan area who regularly commuted to campus using private vehicles. Participants were selected through purposive sampling based on commuting frequency and travel distance criteria. Data were collected using Likert-scale questionnaires and analyzed through descriptive statistics, multiple regression, and path analysis. The findings revealed that both traffic conditions (β = 0.335, p < 0.001) and commuting distance (β = 0.416, p < 0.001) had significant positive effects on driving fatigue, jointly explaining 43.8% of its variance. Furthermore, driving fatigue negatively affected academic motivation (β = −0.495, p < 0.001) with an explained variance of 33.6%. These findings indicate that daily commuting experiences play an important role in shaping students' physical readiness and academic engagement. Therefore, transportation improvements and more flexible academic policies should be considered to better support commuter students.